Chemistry for matriculation - Tan, Yin Toon (Oxford Fajar Sdn Bhd, 2015)
Chemistry for Matriculation Semester 2 Fourth Edition Updated is a comprehensive coursebook written for students studying Chemistry in local matriculation colleges. It is based on the Matriculation Chemistry SK026 syllabus issued by the Matriculation Division, Ministry of Education, Malaysia. This coursebook aims to stimulate students' interest in chemistry and help them gain a firm understanding of important principles and concepts in chemistry. In addition, it helps students prepare for their Chemistry examination.